Electrophysiological Characteristics of Cervical Spinal Stenosis - Yanrong Wang; Yinping Zhan; Xiaolan Jin; Dandan Shen; Ling Wang; Tingting Cao; Hong Jiang (Applied Bionics and Biomechanics)
Objective. To investigate electrophysiological characteristics of patients with cervical spinal stenosis (CSS) due to cervical disc herniation. Methods. A total of 51 patients with CSS diagnosed in our hospital from January 2018 to March 2020 were selected. According to magnetic resonance imaging (MRI), the degree of spinal cord compression was divided into 1-3 grades, namely, group A (MRI grade 1), group B (MRI grade 2), and group C (MRI grade 3), with 17 cases in each group. Subsequently, we analyzed the correlation of the degree of spinal cord compression with the general information, clinical data, and electromyography (EMG) of patients. Results. Compared with group A and group B, group C had the longest disease course [(48.06±17.71) months], the lowest JOA score (4.59±2.15), and the highest number of positive results of EMG (EMG: A/B/C, 25/51/77); there were significant differences among the 3 groups. And group C had the higher number of positive cases of both upper and lower limbs in SEP test compared with the other two groups (SEP: A/B/C: 12/18/29: χ2=7.559, P=0.023). According to correlation analysis, MRI grading had no association with gender, age, and spinal canal diameter/volume but was positively correlated with disease course and negatively correlated with JOA score. Conclusion. This study primarily verifies that higher MRI grade of CSS is associated with longer disease duration and lower JOA score and EMG. The obtained results secondarily demonstrate the correlation between abnormal neurological status and the MRI grade.